Coastal tourism development in Sinop as an emerging rural destination: A preliminary study from the residents perspective - Daskin,Mustafa (2020)
This study proposes to explore the economic, sociocultural, and environmental effects of coastal tourism development in a Turkish context. It adopts a quantitative approach and performed a random sampling technique. The survey data was collected from a sample of local people in Sinop/Turkey and total number of 252 utilizable questionnaires was gathered and analyzed through descriptive statistics. ANOVA test was also applied in order to compute the perceptional differences among demographical groups. The findings demonstrate that while majority of residents have positive perceptions in general, some agree with negative economic, sociocultural, and environmental effects of coastal tourism in the area. Specifically, they perceive that tourism raises the cost of products and services and as a result of an increase in living costs. ANOVA test shows that there were differences between educational groups in negative environmental impacts and age groups in positive economic impacts. In terms of sustainable coastal tourism, the present work procures further addition to tourism literature and also offers beneficial implications to industry practitioners.